THE ESSENTIAL ROLE OF LESSON PLANNING FOR CLINICAL INSTRUCTORS - Mohammed Rasheedan, Ellin (2025)
Lesson planning is a fundamental component of effective clinical instruction, yet it is frequently overlooked by clinical educators. This paper explores the significance of structured lesson planning in clinical education, emphasizing its role in enhancing organization, aligning with learning objectives, improving time management, and promoting student engagement. Through a literature review, we analyze the common reasons why clinical instructors neglect lesson planning, including time constraints, preference for flexibility, lack of pedagogical training, reliance on intuition, and institutional barriers. The discussion highlights strategies to expedite lesson plan development, including the integration of AI tools, standardized templates, and faculty training programs. Furthermore, we address the challenges of lesson planning and propose solutions to ensure ethical and best-practice compliance in clinical education. The paper concludes by presenting a standardized lesson plan template to guide clinical instructors in structuring their teaching sessions effectively.